Prevalence of Chronic Ankle Instability in High School and Division I Athletes. Issue 1 (February 2014) - Tanen, Leah; Docherty, Carrie L.; Van Der Pol, Barbara; Simon, Janet; Schrader, John
Objective . The purpose of this study was to determine the prevalence of chronic ankle instability among high school and collegiate athletes. Design . Descriptive epidemiological survey. Methods . Athletes from four high schools and a division I university were contacted to participate. For collegiate athletes, a questionnaire packet was distributed during preparticipation physicals. For high school athletes, parental consent was obtained and then questionnaires were distributed during preparticipation physicals, parent meetings, or individual team meetings. All athletes completed the Cumberland Ankle Instability Tool for both their left and right ankles. Subjects also provided general demographic data and completed the Ankle Instability Instrument regarding history of lateral ankle sprains and giving way. Athletes were identified as having chronic ankle instability if they scored less than 24 on the Cumberland Ankle Instability Tool. Results . Of the 512 athletes who completed and returned surveys, 23.4% were identified as having chronic ankle instability. High school athletes were more likely to have chronic ankle instability than their collegiate counterparts (P < .001). Chronic ankle instability was more prevalent among women than among men in both high school (P = .01) and collegiate settings (P = .01). Conclusions . Findings of this study revealed differences in the distribution of chronic ankle instability that warrant further study. Levels of Evidence: Prognostic, Level IV, case series